Dual regulation of microglia and neurons by Astragaloside IV‐mediated mTORC1 suppression promotes functional recovery after acute spinal cord injury - Lin, Jialiang (J Cell Mol Med, 2019)
Inflammation and neuronal apoptosis contribute to the progression of secondary injury after spinal cord injury (SCI) and are targets for SCI therapy; autophagy is reported to suppress apoptosis in neuronal cells and M2 polarization may attenuate inflammatory response in microglia, while both are negatively regulated by mTORC1 signalling. We hypothesize that mTORC1 suppression may have dual effects on inflammation and neuronal apoptosis and may be a feasible approach for SCI therapy. In this study, we evaluate a novel inhibitor of mTORC1 signalling, Astragaloside IV (AS‐IV), in vitro and in vivo. Our results showed that AS‐IV may suppress mTORC1 signalling both in neuronal cells and microglial cells in vitro and in vivo. AS‐IV treatment may stimulate autophagy in neuronal cells and protect them against apoptosis through autophagy regulation; it may also promote M2 polarization in microglial cells and attenuate neuroinflammation. In vivo, rats were intraperitoneally injected with AS‐IV (10 mg/kg/d) after SCI, behavioural and histological evaluations showed that AS‐IV may promote functional recovery in rats after SCI. We propose that mTORC1 suppression may attenuate both microglial inflammatory response and neuronal apoptosis and promote functional recovery after SCI, while AS‐IV may become a novel therapeutic medicine for SCI.